2020
DOI: 10.3390/su12166377
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Sustainable Geopolymer Composite Using Automatic Identification Technology

Abstract: Geopolymers are materials prepared from alkaline-activated cement without a calcium constituent. They are synthetic materials based on aluminosilicates. The main advantage of these environmentally friendly materials is that they save mineral resources and due to being free of calcium constituents, and only a small amount of CO2 emissions are released into the environment. The circular economy model of sustainable development of new composite materials will ensure the competitiveness of industries, their stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…It puts pressure on all manufacturing and non-manufacturing companies, using different approaches to effective team building, automation and robotics, and effective management. As the development and implementation of warehousing logistics expanded, companies found that up to 40% of costs in this area could only be saved by efficiently managing and streamlining material flows without the real need to purchase new equipment [21,22]. The development of advanced simulation systems has opened up new possibilities and significantly supported the trend to rationalize warehousing activities, reducing costs and improving business performance [23].…”
Section: Literature Review and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…It puts pressure on all manufacturing and non-manufacturing companies, using different approaches to effective team building, automation and robotics, and effective management. As the development and implementation of warehousing logistics expanded, companies found that up to 40% of costs in this area could only be saved by efficiently managing and streamlining material flows without the real need to purchase new equipment [21,22]. The development of advanced simulation systems has opened up new possibilities and significantly supported the trend to rationalize warehousing activities, reducing costs and improving business performance [23].…”
Section: Literature Review and Methodologymentioning
confidence: 99%
“…Each used block represents the part of the process or operation in the simulation model. The blocks have its unique icon and name there expresses its basic usage within the model [22,23]. The created simulation model is the model of discrete simulation created from blocks taken from the ''Discreet Event'' and ''Plotter'' libraries, Fig.…”
Section: Simulation Model Of Selected Logistics Activity In Warehousementioning
confidence: 99%
See 1 more Smart Citation
“…If the M L values from Table 3 and the P TS traffic performance values from Table 4 obtained by the calculation are compared (the values are bold marked) for the loading sites P1 and P3, they are almost the same. The values are different for place P2, which is due to the form of calculation (1) and (4).…”
Section: Tables 3 and 4 Andmentioning
confidence: 99%
“…The essence of sustainable development is the efficient use of natural resources [1]. The mining and processing industry of raw materials contributes to a huge share in the national economy and delivers an invaluable resource for modern civilization [2].…”
Section: Introductionmentioning
confidence: 99%